Antagonism of Chaetomium globosum to Drechslera sorokiniana, the spot blotch pathogen of wheat - R. AGGARWAL, PREM DUREJA*; D.V. SINGH, S.K. BISWAS, K.D. SRIVASTAVA, (Indian Phytopathology, 2002)
Interaction between Chaetomium globosum and Drechslera sorokiniana [Cochliobolus sativus] produced inhibition zone, indicating biocontrol mechanism of Ch. globosum through antibiosis. Fractionation of ethyl-acetate extract of culture filtrate of Ch.globosum by TLC revealed 4-5 bands of different Rf values on silica gel-coated plates, indicating the involvement of antifungal metabolites or mycolytic enzymes. Crude extracts purified by column chromatography and bioassay test with 1000 ppm of concentrate antagonised conidia of Co. sativus and drastically reduced their germination. Scanning electron microscopy of inoculated leaves sprayed with 0.2% of the antifungal compound showed distortion in conidial walls and disordered mycelial growth of the pathogen. Foliar spray of the compound at 0.2% controlled spot blotch lesions in wheat and revealed a stimulatory effect on plant growth.